Resting-state functional magnetic resonance imaging study on cerebrovascular reactivity changes in the precuneus of Alzheimer’s disease and mild cognitive impairment patients - Tang, Xue; Wang, Luoyu; Feng, Qi; Hu, Hanjun; Zhu, Yidi; Liao, Zhengluan; Ding, Zhongxiang; Xu, Xiufang (Scientific reports, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by memory impairment and cognitive decline, ultimately culminating in dementia. This study aims to evaluate cerebrovascular reactivity (CVR) and functional connectivity (FC) in patients with AD and mild cognitive impairment (MCI) using resting-state functional magnetic resonance imaging (rs-fMRI), bypassing the requirement for hypercapnia. The study cohort comprised 53 AD patients, 38 MCI patients, and 39 normal control (NC) subjects. CVR is derived by extracting signals within specific frequency bands of rs-fMRI. This study compares the differences in CVR and FC among the three groups, using the brain regions with CVR differences as region of interest (ROI) for FC analysis. The correlation between CVR and FC and cognitive scale score was discussed. Compared with NC subjects, AD patients exhibited a decrease in CVR in the PCUN.L, whereas MCI patients showed an increase in CVR in the PCUN.R. With PCUN.L as ROI, FC in PCUN.R decreased in AD patients, and FC in SFGmed.R and other brain regions increased in MCI patients compared with NC subjects. The results of the correlation analysis indicate that CVR in all patients, as well as FC with the PCUN.L as the ROI to the PCUN.R and SFGmed.R, show positive correlations with MMSE and MoCA scores. These results suggest that there are significant differences between CVR and FC with CVR differential brain regions as ROI among the AD, MCI, and NC groups, which may help to explain the hemodynamic mechanism. CVR obtained with rs-fMRI may be a potential biomarker for assessing cognitive impairment.